ANALISIS SEVEN CONTRUCTS INNOVATION MANAGEMENT MEASUREMENT FRAMEWORK PADA LAYANAN E-SCHOOL BUS CARD DI KOTA SURABAYA - Alfidioni Aprilia Aryanti; Eva Hany Fanida (Universitas Negeri Surabaya, 2021)
The Surabaya City Transportation Service has created an innovative e-School Bus Card service that aims to overcome the ineffectiveness of manual attendance that occurs on Surabaya City school buses and facilitate attendance for students who use the Surabaya City school bus. The existence of the e-School Bus Card service, students who use the Surabaya City school bus do not need to queue to fill in attendance, the time required is very short because the Surabaya City school bus officer simply does the tapping (pasting the card with the tools provided by the Surabaya City Transportation Service). So the purpose of this research is to find out and describe the innovation of e-School Bus Card services at the Surabaya City Transportation Service. This study uses descriptive qualitative research methods. The focus of this research is the theory of innovation development by analyzing innovation using the theory of Seven Contructs from the IMMF which consists of Inputs, Knowledge Management, Innovation Strategy, Organization and Culture, Portfolio Management, Project Management, Commercialization (Murrase et al, 2018). Data collection techniques done by means of observation, documentation and interviews. Based on the results of research conducted by researchers, it shows that, there are several reasons or considerations in making decisions for e-School Bus Card service innovations at the Surabaya City Transportation Service. The need to meet the innovation of the e-Bus School Card service is also simple and maximizes existing services. In addition, the Surabaya City Transportation Service also collaborates with several parties to attract students to use the Surabaya City school bus as a means of transportation for school activities and make it easier for students to get an e-School Bus Card. The serviceinnovation has been well done in overcoming the previous problems but needs to be improved again to maximize the service innovation. Keywords: Analysis, Service, e-gov, e-School Bus Card Dinas Perhubungan Kota Surabaya telah menciptakan sebuah inovasi layanan e-School Bus Card yang bertujuan untuk mengatasi kurang efektifnya absensi secara manual yang terjadi pada bus sekolah Kota Surabaya dan mempermudah absensi untuk siswa siswi yang menggunakan bus sekolah Kota Surabaya. Adanya layanan e-School Bus Card siswa siswi yang menggunakan bus sekolah Kota Surabaya tidak perlu antri untuk mengisi absensi, waktu yang dibutuhkan sangat singkat karena petugas bus sekolah Kota Surabaya cukup melakukan tapping (menempelkan kartu dengan alat yang telah disediakan oleh Dinas Perhubungan Kota Surabaya). Sehingga tujuan dari penelitian ini adalah untuk mengetahui dan mendeskripsikan inovasi layanan e-School Bus Card di Dinas Perhubungan Kota Surabaya. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Fokus penelitian ini ialah teori perkembangan inovasi dengan menganalisis inovasi menggunakan teori Seven Contructs from the IMMF yang terdiri dari Inputs, Knowledge Management, Innovation Strategy, Organization and Culture, Portofolio Management, Project Management, Commercialization (Murrase et al, 2018).Teknik pengumpulan data dilakukan dengan cara observasi, dokumentasi dan wawancara. Berdasarkan hasil penelitian yang dilakukan peneliti menunjukkan bahwa, terdapat beberapa alasan atau pertimbangan dalam mengambil keputusan inovasi layanan e-School Bus Card di Dinas Perhubungan Kota Surabaya. Kebutuhan dalam memenuhi inovasi layanan e-Bus School Card juga sederhana dan memaksimalkan layanan yang sudah ada. Inovasi layanan tersebut sudah baik dilakukan dalam mengatasi masalah sebelumnya namun perlu ditingkatkan lagi untuk memaksimalkan inovasi layanan tersebut. Kata Kunci: Analisis, Layanan, e-gov, e-School Bus Card